Efforts to Improve Student Learning Outcomes Through the Application of the Course Review Horay Method to Students in Class IVC SDIT Jumapolo - Yatni, Yatni (Universitas Sebelas Maret, 2022)
This research is motivated by the habit of teaching teachers not using various models or only using conventional methods in the form of lectures, with the result that there are still many students who do not meet the KKM. The purpose of this study was to find out how much the thematic learning outcomes of the Beautiful Togetherness Theme of Sound Reflection Science material through the Course Review Horay (CRH) learning model. The learning model used in this study is with 2 cycles. The increase in student learning outcomes in learning using the Course Review Horay (CRH) learning model is proven by the average classical mastery in the pre-cycle of 50.00, in cycle I it becomes 60.80 and in cycle II it becomes 81.12, so it can be concluded that through the Course Review Horay (CRH) learning model can improve Thematic learning outcomes in IVC class SDIT Jumapolo students.